The Effect of an Increase in the Interest Rate and Inflation on Personal Finances in Islamic Republic of Pakistan - Ullah, Naqeeb; Asghar, Umair (2023)
Increasing rate of inflation has been one of the most essential problems, especially after period of Covid-19 and Russia Ukraine War, which also tends to increase in the rate of interest rate. Therefore, researcher has particularly analysed the impact of inflation and interest rate on personal finances. Primary quantitative research method has been used using survey questionnaire, and information has been collected from 100 households using convenience sampling. For data analysis, statistical tools (. e. descriptive, reliability, and inferential statistics) were used via using SPSS software. It shows that both male and female from different age group has been participated in the current research. Hence, findings revealed that inflation rate has a negative influence on personal finance, while interest rate has a positive influence on personal finance. Findings in the current research have been primarily focused on primary quantitative research that can be used in secondary studies in future for in-depth analysis. Additionally, consideration of control variables (i.e., income, accessibility to banking institutions, and facilities provided for personal finances) can also be used to avoid biased results.